A new species of frogfish of the genus Histiophryne (Teleostei: Lophiiformes: Antennariidae) from Queensland, Australia - Arnold, Rachel J.; Pietsch, Theodore W. (Zootaxa, 2011)
Histiophryne maggiewalker, a new species of frogfish of the teleost order Lophiiformes, family Antennariidae, is described from six specimens collected in shallow waters off Queensland, Australia. The new taxon differs from its congeners in having a relatively long illicium and esca, the latter expanded distally, more or less rectangular; and genetic divergence in the nuclear recombination activation gene-2 (RAG2) and cytochrome oxidase-I (COI) genes. Members of the new species are black with a reticulate patterning discernible only with aid of a dissecting scope; or white with light brown spots. The new species is described and compared with its congeners.